World Congress on Communication for Development : Lessons, Challenges, and the Way Forward - The Communication Initiative (Washington, DC: World Bank, 2012)
The first World Congress on Communication for Development (WCCD) took place in Rome, Italy, on October 25-27, 2006. The main goal of the WCCD was to position and promote the field of Communication for Development in the overall agenda of development and international cooperation. Toward this end, three types of stakeholders, who rarely interact, gathered in Rome: academics, practitioners, and policy and decision makers. The interaction and exchange of perspectives among these three groups served to enhance the overall understanding of the field of Communication for Development by a broader audience.